Estimation of horizontal spatial specifications for ideal head-mounted displays in practical conditions - Miyashita, Yamato; Harasawa, Masamitsu; Hara, Kazuhiro; Sawahata, Yasuhito; Komine, Kazuteru (Frontiers in Virtual Reality, 2024)
This study presents the horizontal spatial specifications required for developing ideal head-mounted displays (HMDs) that provide visual experiences indistinguishable from those obtained without wearing HMDs. We investigated the minimum specifications for pixel density and field of view (FoV) such that users cannot perceive any degradation in these aspects. Conventional studies have measured visual acuity in the periphery and FoV size without eye movement. However, these results are not sufficient to determine the spatial specifications because users may notice a degradation in the quality of images displayed in the periphery when shifting their gaze away from the front. In this study, we measured visual characteristics under practical conditions, wherein participants moved their eyes naturally in coordination with their head movements, as observed when viewing natural scenes. Using a cylindrical display that covered the participant's entire horizontal visual field with high resolution images, we asked participants to identify degraded spatial resolution or narrowed FoV. Results showed that ideal HMDs do not have to provide spatial frequency components above 0.5 and 2 cycles per degree outside the visual fields of approximately 210° and 120° horizontally, respectively. These results suggest that a resolution equivalent to one-fifteenth of the frontal area is sufficient for the lateral areas of the head. In addition, we found that ideal HMDs require a FoV of at least 240°. This is considerably smaller than a naive estimate of 310° based on previous studies, obtained by integrating the FoV size during fixation and the movable range of the eyes. We believe that these findings will be helpful in developing ideal HMDs.